Variable Pringle Maneuvers and Effect on Intestinal Epithelium in Rats. A Pilot Experimental Study in Rats. - Dimitrios Dimitroulis; Demetrios Moris; Emmanouil Pikoulis; Eleftherios Spartalis; Georgios Kontadakis; Bart Vrugt; Serena Valsami; Gregory Kouraklis (PLoS ONE, 2015)
It is observed that combined liver and colon surgery especially when this includes major liver resection with Pringle maneuver (PM) performance does not have a favorable outcome. Aim of our experimental study is to investigate the impact of portal triad occlusion on the large bowel and intra-abdominal inflammation and potent protective effects of the variants of (PM) in the combined surgical cases.Forty-four rats were divided into four groups. In group A (control group), 1cm of the left partial colon was resected and then an end-to-end anastomosis was performed. In group B, a continuous PM for 30 minutes was performed followed by resection of 1cm of the left colon and an end-to-end anastomosis. In group C, the left colonic resection and anastomosis was performed after intermittent PM (IPM), which was 10 minutes PM followed by 5 minutes reperfusion repeated for three circles. In group D, an ischemic preconditioning for 10 minutes was initially performed followed by 5 minutes reperfusion and then continuous PM for 30 minutes. Finally the rats in group D underwent a 1cm left colonic resection and an end-to-end anastomosis.The percentage of colitis was higher in the B group (P = 0,19). The percentage of inflammation was not significantly higher even when we compared all "occlusion" groups (B+C+D) with the sham group. No evidence of pancreatitis was found in the sham group whereas amylase and lipase levels were higher in Groups B, C and D together (P = 0,0267). The comparison of group A to group B showed a significant difference (P = 0,0014) caused by continuous PM for 30 minutes, but there was no such result after IPM.Major liver resections are performed with PM in order to minimize intra-operative blood loss. In the combined cases of colon surgery and major liver resections where PM is needed our results showed that IPM presents with better outcome and could be preferred compared with the other PM variants.